ANALISIS PENGETAHUAN KOMPETENSI PROFESIONAL MAHASISWA CALON GURU SEKOLAH DASAR - Auliaturrahmah, Syinta; Suroyo, Suroyo; Hermita, Neni; Alim, Jesi Alexander; Ibrahim, Bedriati (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
This study aims to describe and find out how professional competency knowledge of elementary school teacher candidates for PGSD FKIP Riau University students. The research method in this study is a survey method. The type of data used is quantitative data in the form of numbers and primary data obtained through a distributed google form questionnaire. Data collection techniques are carried out by distributing questionnaires or questionnaires that have previously been validated by the validator. The data analysis technique in this research is descriptive quantitative with statistical analysis. The data taken is then calculated the percentage of data from each indicator, then interpret the percentage score and analyze each indicator. This research involved 120 active students of class 2017, 2018, 2019, and 2020 PGSD FKIP Riau University. The results of the overall data recapitulation of each indicator of professional competence knowledge of prospective elementary school teacher students are 68.01% with a good category. It can conclude that the knowledge of the professional competence of prospective elementary school teacher students can be categorized as good. This research can be expected to become a guideline and evaluation for related parties in need. The results of this study are also expected to be used as study material for other researchers in analyzing the professional competence knowledge of prospective elementary school teachers.